Pozycja prawna notariusza w sprawach spadkowych o charakterze transgranicznym Glosa do wyroku Trybunału Sprawiedliwości Unii Europejskiej w sprawie C-658/17 WB - Konieczna, Kinga (Problemy Prawa Prywatnego Międzynarodowego, 2020)
The commentary presents an analysis of a thesis presented by the Court of Justice of the European Union in Judgment of 23rd of May 2018. The question referred to the Court in case C-658/17 WB concerned legal definition of a ‚court’ and legal classification of the national deed of certification of succession under the provisions of Regulation (EU) No 650/2012. The Judgment states that notary in Poland that draw up a deed of certificate of succession at the unanimous request of all the parties, does not constitute a ‚court’ within the meaning of that provision. Subsequently, a deed drawn up by such authority does not constitute a ‘decision’ within the meaning of that provision. The Judgment is particularly relevant since its impact extends to national certificates of succession issued by notaries in other countries, that are part of the Latin part notary system. In conclusion it is indicated, that the Judgment rendered by Tribunal, although highly rightful, relates to merely one of numerous issues concerning use of authentic documents in cross-border succession cases.